The Contingent Tariff of the Special Safeguard Mechanism: What Happens When Markets are Imperfectly Competitive?. (14th October 2015) - MacLaren, Donald
Abstract: Contingent tariffs for agri‐food commodities have been proposed as a Special Safeguard Mechanism (SSM) in the Doha Round negotiations by the G33 group of countries as an instrument to control downward spikes in their border prices and/or surges of imports. The objective is to safeguard the livelihood security of farm households in poor countries. To date, most analysis of such tariffs uses stochastic partial equilibrium models with perfect competition. Yet in many markets for such commodities, imperfectly competitive market intermediaries play an important role in determining producers' prices, as do state trading enterprises (STEs). A stochastic partial equilibrium model of a typical importing country situation is specified in which there are either imperfectly competitive domestic intermediaries with a contingent tariff or an STE. The role of these intermediaries in influencing price behaviour and livelihood security in the presence of contingent tariffs alters the conclusion based on models of perfect competition. Using Monte‐Carlo simulation, it is shown that the efficacy of a contingent tariff is substantially reduced as the number of firms declines because increasingly they absorb the tariff, and the procurement price and producer surplus do not increase to the extent that they do under perfect competition.